Indigo - Weston, Christine (London The Reprint Society, 1946)
"The story of the friendship of three men - one the son of French parents, owners of an indigo plantation; a young Hindu, son of a westernized Hindu lawyer; and the son of an English army officer. The story opens in the 1890's and continues until the end of the First World War and the beginning of the struggle for Indian liberty."
Keywords: Fiction : Historical